Barriers and Facilitators of Community Integration of People With Spinal Cord Injuries Living in Low and Middle-Income Countries: A Systematic Review - Meenakshi Mohan; Roumi Deb (Function and Disability Journal, 2022)
Background and Objectives: Spinal cord injury (SCI) is an irreversible and potentially life-altering event that creates poor economic conditions. The SCI healthcare model has shifted more towards patient-centered care, which focuses on the issues that affect the quality of life and community integration of people with such disabilities. This systematic review was conducted to identify the factors influencing the community integration of SCI individuals in low- and middle-income countries. Methods: Three databases of Scopus, PsycINFO, and PubMed were searched with the keywords of “spinal cord injury”, “tetraplegia”, “paraplegia”, and “challenges” for relevant articles published from 2010 to 2020. Boolean operators “OR” and “AND” were used between the keywords, and cross-linking methods were applied to get better results. The quality assessment of the included studies was analyzed by the Critical Appraisal Skills Programme (CASP) and Thomas tool. The extracted data included demographic details, sample size, results, and outcome measures. Results: A total of 26 peer-reviewed studies were included in the review. The evidence extracted was classified into six categories that influence the community participation (either positive or negative) of SCI individuals. Conclusion: The review revealed more barriers in the form of health-related, environmental, psychological, and social issues that hinder the community reintegration of individuals with SCI compared to facilitators such as spirituality, family/friends support, self-efficacy and resilience. Most research studies highlighted specific environmental obstacles in terms of accessibility and affordability. By working on these challenges, the authorities can enhance community integration of the SCI population in low- and middle-income countries.